A Phase I Study of the Safety and Pharmacokinetics of Higher-Dose Icotinib in Patients With Advanced Non-Small Cell Lung Cancer. (27th October 2016) - Liu, Jian; Wu, Lihua; Wu, Guolan; Hu, Xingjiang; Zhou, Huili; Chen, Junchun; Zhu, Meixiang; Xu, Wei; Tan, Fenlai; Ding, Lieming; Wang, Yinxiang; Shentu, Jianzhong
Abstract : Lessons Learned : This phase I study evaluated the maximum tolerated dose, dose-limiting toxicities, safety, pharmacokinetics, and efficacy of icotinib with a starting dose of 250 mg in pretreated, advanced non-small cell lung cancer patients. We observed a maximum tolerated dose of 500 mg with a favorable pharmacokinetics profile and antitumor activity. These findings provide clinicians with evidence for application of higher-dose icotinib. Background: Icotinib, an oral epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor, has shown favorable tolerability and antitumor activity at 100–200 mg in previous studies without reaching the maximum tolerated dose (MTD). In July 2011, icotinib was approved by the China Food and Drug Administration at a dose of 125 mg three times daily for the treatment of patients with locally advanced or metastatic non-small cell lung cancer (NSCLC) after failure of at least one platinum-based chemotherapy regimen. This study investigated the MTD, tolerability, and pharmacokinetics of higher-dose icotinib in patients with advanced NSCLC. Methods: Twenty-six patients with advanced NSCLC were treated at doses of 250–625 mg three times daily The EGFR mutation test was not mandatory in this study. Results: Twenty-four (92.3%) of 26 patients experienced at least one adverse event (AE); rash (61.5%), diarrhea (23.1%), and oral ulceration (11.5%) were most frequent AEs. Dose-limiting toxicities were seen in 2 of 6 patients in the 625-mg group, and the MTD was established at 500 mg. Icotinib was rapidly absorbed and eliminated. The amount of time that the drug was present at the maximum concentration in serum (Tmax ) ranged from 1 to 3 hours (1.5–4 hours) after multiple doses. The t1/2 was similar after single- and multiple-dose administration (7.11 and 6.39 hours, respectively). A nonlinear relationship was observed between dose and drug exposure. Responses were seen in 6 (23.1%) patients, and 8 (30.8%) patients had stable disease. Conclusion: This study demonstrated that higher-dose icotinib was well-tolerated, with a MTD of 500 mg. Favorable antitumor activity and pharmacokinetic profile were observed in patients with heavily pretreated, advanced NSCLC.